Function‐Oriented and Modular (+/−)‐cis‐Pseudoguaianolide Synthesis: Discovery of New Nrf2 Activators and NF‐κB Inhibitors. Issue 17 (26th February 2021) - Emmetiere, Fabien; Ratnayake, Ranjala; Schares, Henry A. M.; Jones, Katherine F. M.; Bevan–Smith, Emily; Luesch, Hendrik; Harki, Daniel A.; Grenning, Alexander J.
Abstract: Described herein is a function‐oriented synthesis route and biological evaluation of pseudoguaianolide analogues. The 10‐step synthetic route developed retains the topological complexity of the natural product, installs functional handles for late‐stage diversification, and forges the key bioactive Michael acceptors early in the synthesis. The analogues were found to be low‐micromolar Nrf2 activators and micromolar NF‐κB inhibitors and dependent on the local environment of the Michael acceptor moieties. Abstract : Covalent modification is back, Jack ! Function‐oriented synthesis and biological evaluation of pseudoguaianolide analogues is described. The key hydroazulene framework is established by enyne metathesis, functional groups are in place to rapidly establish the key electrophilic warheads, and the route has the potential for preparing analogues in both convergent and divergent fashion. The analogues were found to be low‐micromolar Nrf2 activators and micromolar NF‐κB inhibitors.